Developing Android-Based Educational Puzzle Game For Biology To Improve Students' Cognitive Ability - Haka, Nukhbatul Bidayati; Handayani, Putri Wiwin; Anggoro, Bambang Sri; Hamid, Abdul (Biosfer: Jurnal Tadris Biologi, 2021)
This research aims to determine the development, feasibility, and effectiveness of an android-based educational puzzle game for biology learning. This research is a research and development (R&D) with Brog and Gall procedure up to the ninth stage. The instruments employed are the media expert validation questionnaire, the language expert validation questionnaire, the material expert validation questionnaire, the student response questionnaire, cognitive ability tests, and documentation. Based on the validation by the experts, the media experts validation percentage was 98.91%, the language expert validation percentage was 92.05%, the material expert validation percentage was 98.5%, and the students' response questionnaire percentage was 85.75%. All the results were categorized as highly feasible. Furthermore, the effectiveness of the product based on the independent sample t-test was tobserved (5. 57) was higher than tcritical (1.71) with an average N-gain value in the experimental class of 0.64 and the control class of 0.40. Based on the assessment, the Android-based educational puzzle game for biology on virus material can improve students’ cognitive abilities